ackson solved the problem 3x-8=2(2x-7) using the following steps: STEP 1: Use Distributive Property to get 3x-8=4x-14 STEP 2: Use Addition Property of Equality to get 3x = 4x-14+8 STEP 3: Combine Like Terms to get 3x = 4x-6 STEP 4: Use Subtraction Property of Equality to get 3x-4x= -6 STEP 5: Combine Like Terms to get (-x)=-6 What is the last step? A. Use Property of Equality to get x= (-6) B. Divide both sides by -1 to get x=6 C. Divide both sides by -1 to get x= (-6) D. Use Multiplication Property of Equality to get x=6

1 answer

B. Divide both sides by -1 to get x=6
Similar Questions
    1. answers icon 1 answer
  1. QuestionMs, Wilson is solving the equation: 7x−4=3(4x+12) . Here are her steps so far Step 1 (the Distributive Property):
    1. answers icon 1 answer
  2. Jackson solved the problem 3x-8=2(2x-7) using the following steps:STEP 1: Use Distributive Property to get 3x-8=4x-14 STEP 2:
    1. answers icon 4 answers
  3. Multiple Choice QuestionJackson solved the problem 3x-8=2(2x-7) using the following steps: STEP 1: Use Distributive Property to
    1. answers icon 1 answer
more similar questions